BERDAYA SAING DI ERA DIGITAL: PENINGKATAN UMKM DODOL KENTANG KERINCI MELALUI MODERNISASI DAN EDUKASI DALAM MENJAGA NILAI-NILAI TRADISIONAL - Ramadani, Ramadani; Zebua, Dinyah Rizki Yanti; Novinovrita, Novinovrita; Saputri, Utari Aulia Tianda (RANGGUK: Jurnal Pengabdian Kepada Masyarakat, 2023)
In facing the challenging digital era, Small and Medium Enterprises (SMEs) specializing in Dodol Kentang in Kerinci experience pressure to remain competitive. This research explores the potential enhancement of competitiveness for Dodol Kentang SMEs by implementing modernization and educational strategies. The primary focus of this research is to preserve traditional values while addressing them innovatively. Through the Participatory Action Research (PAR) approach, business owners, academics, and local communities collaborate to identify constraints, formulate common goals, and plan and implement improvement measures. Education is a key component in equipping business owners with knowledge of modernization and the use of digital technology, aimed at improving production efficiency, online marketing, and business management. Product modernization is carried out through packaging evaluation, halal labeling, and the addition of flavor variations. These steps are expected to make Dodol Kentang SMEs more relevant in the national market while preserving the essence of traditional values. The results of this research are expected to contribute positively to the sustainability of Dodol Kentang SMEs, enhance their competitiveness in the digital era, and support the preservation of traditional cultural heritage in Kerinci Regency.